Identification of Metabolites Associated with Superior Heat Tolerance in Thermal Bentgrass through Metabolic Profiling. Issue 4 (1st July 2013) - Xu, Yan; Du, Hongmei; Huang, Bingru
ABSTRACT: Heat stress affects various metabolic processes and limits the growth of cool‐season plants. The objectives of this study were to compare metabolite profiles of two Agrostis species exhibiting differential heat tolerance and identify key metabolites associated with heat tolerance in cool‐season grass species. Heat‐tolerant thermal bentgrass ( Agrostis scabra Willd.) and heat‐sensitive creeping bentgrass ( Agrostis stolonifera L.) were exposed to 40/38°C (day/night) (heat stress) or 20/18°C (day/night) (control) for 10 d in growth chambers. Polar metabolites (remaining in the methanol–water phase and separated from those in the chloroform phase during extraction) from leaves and roots were quantified separately using gas chromatography–mass spectrometry. The major heat‐responsive metabolites in the two Agrostis grass species included organic acids (lactic acid, threonic acid, and aminomalonic acid) and sugars (glucose, fructose, sucrose, and maltose) in leaves and amino acids (valine, alanine, proline, aspartic acid, γ‐aminobutyric acid, and asparagines), organic acids (threonic acid, gluconic acid, and citric acid), and sugars (fructose, floridoside, and turanose) in roots. Compared to heat‐sensitive A. stolonifera, heat‐tolerant A. scabra maintained higher accumulation or lesser degradation of soluble monosaccharides (fructose and glucose) necessary for energy production, branched‐chain amino acids (valine and isoleucine) used in secondary signaling, and 5‐oxoproline and putrescine for antioxidant defense as well as sucrose, proline, and myo ‐inositol involved in osmotic regulation. The results suggest that maintaining active cellular metabolisms for energy production, stress signaling, antioxidant protection, and osmoregulation could contribute to superior heat tolerance in cool‐season grass species.